Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.micres.2017.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of two carrier materials for phosphate solubilizing biofertilizers and their effect on growth of wheat (Triticum aestivum L.)

Abstract: Biofertilizers are usually carrier-based inoculants containing beneficial microorganisms. Incorporation of microorganisms in carrier material enables easy-handling, long-term storage and high effectiveness of biofertilizers. Objective of the present study was to assess enriched biogas sludge and soil as biofertilizer carriers on growth and yield of wheat. Six phosphate solubilizing strains were used in this study. Three phosphate solubilizing strains, 77-NS2 (Bacillus endophyticus), 77-CS-S1 (Bacillus sphaeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(55 citation statements)
references
References 32 publications
1
49
1
4
Order By: Relevance
“…The pH, TOC, CEC, and texture values, which ranged from 7.9 to 8.0, 1.1%, and 13.2 to 13.7 meq 100 g -1 , respectively, were similar during the experiment and were not affected by the biocontroller application. These results are similar to those reported by Mukhtar et al (2017), who found no differences in pH and texture after applying phosphate-solubilizing biofertilizer to a wheat crop. In contrast, Singh and Reddy (2012) reported an increase in soil organic C in bio-inoculated soil compared with the control.…”
Section: Effect Of Pseudomonas Fluorescens On Soil Propertiessupporting
confidence: 92%
“…The pH, TOC, CEC, and texture values, which ranged from 7.9 to 8.0, 1.1%, and 13.2 to 13.7 meq 100 g -1 , respectively, were similar during the experiment and were not affected by the biocontroller application. These results are similar to those reported by Mukhtar et al (2017), who found no differences in pH and texture after applying phosphate-solubilizing biofertilizer to a wheat crop. In contrast, Singh and Reddy (2012) reported an increase in soil organic C in bio-inoculated soil compared with the control.…”
Section: Effect Of Pseudomonas Fluorescens On Soil Propertiessupporting
confidence: 92%
“…Rhizosum PK ® is a biofertilizer containing i.a. Bacillus megaterium and Frateuria aurantia which were found to exhibit potassium-mobilizing properties [49][50][51]. A study conducted by Mengual et al [52] showed that the introduction of microbial inoculants to the soil positively the affected activities of urease, protease and β-glucosidase with significant changes occurring in the case of urease and protease.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the genus Staphylococcus (S. equorum, S. haemolyticus, and S. saprophyticus) were identified from the rhizosphere of Salsola and Atriplex and lake-bank soils. They are moderately halophilic strains and play an important role in plant growth and biodegradation of hemicelluloses and lipases [43,44]. Bacterial isolates related to Kocuria and Streptomyces were identified from the rhizosphere of halophytes as well as from the non-rhizospheric soils.…”
Section: Discussionmentioning
confidence: 99%